1975
DOI: 10.3146/i0095-3679-2-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Electronic Color Sorting and Hand Picking to Remove Aflatoxin Contaminated Kernels from Commercial Lots of Shelled Peanuts1

Abstract: Samples (200-lb) from 40 commercial lots of shelled peanuts which contained an average concentration of 48 parts-per-billion aflatoxin were sorted with an electronic color sorter 3 to 5 times and then hand picked in an attempt to remove discolored kernels which usually contain higher concentrations of aflatoxin than other kernels. Prediction equations indicated that cumulative removal of 2, 4, 6, 8 and 10 % of the kernels from each sample by electronic sorting would remove an average of 16, 28, 37, 45 and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0
2

Year Published

1980
1980
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 1 publication
2
14
0
2
Order By: Relevance
“…The color sorting results were also consistent with results reported by other researchers (2,5,18,49). Generalizing the results of this study to the problem of aflatoxin control in peanuts introduces yet another potential source of sampling error.…”
Section: Resultssupporting
confidence: 95%
“…The color sorting results were also consistent with results reported by other researchers (2,5,18,49). Generalizing the results of this study to the problem of aflatoxin control in peanuts introduces yet another potential source of sampling error.…”
Section: Resultssupporting
confidence: 95%
“…However, hand sorting has been optimised only for high-value crops and is being used successfully by exporters from the developing world taking advantage of the availability of relatively cheap labour (Galvez et al 2002(Galvez et al , 2003Derlagen & Phiri 2012). In fact previous research conducted in the 1970-90s demonstrated the supremacy of hand sorting over electronic colour sorting technology in reducing aflatoxin levels in peanut and almonds (Dickens & Whitaker 1975;Schade et al 1975;Pelletier & Reizner 1992). In spite of the legendary history of hand sorting and its successes in mycotoxin management in export commodities the technology remains underutilised in the management of mycotoxins in subsistent food commodities.…”
mentioning
confidence: 94%
“…2). A segregation system by electronic sorting may be feasible for hand picked selected (HPS) groundnuts which are homogeneous as to variety and appearance (colour).…”
Section: Specific Decontamination Nethodsmentioning
confidence: 99%